Dinâmica da ocupação do solo bacia do Rio Itiquira, Mato Grosso, Brasil - Oka-Fiori, Chisato; Fiori, Alberto Pio; Hasui, Yociteru [UNESP] (My University, 2003)
The study area corresponds to the basin of the Itiquira river high course, totalling 5,361km2. In this area a study of the environmental dynamics was made, applying SIG techniques and satellite images of the years 1966, 1985 and 1996. In 1966 the areas of natural vegetation (forests and groves) occupied 90.64% of the total of the area, which was diminished to 60.57% in 1985 and to only 36.66% in 1996. In this process, 289,382ha of a total of 485,928ha of natural vegetal covering had been lost. At the same time, the agrarian surfaces (agriculture and pasture) that occupied only 0.52% of the total area in 1966, increased to 34.89% in 1985 and to 59.04% in 1996. In 30 years there was an increase of 313,725ha of cultivated lands, corresponding to about 113 times the land occupation of the year of 1966 (2,798ha). The areas classified as urban show a gradual increase since 1966, from 39ha in 1996 to 58ha in 1985, and to 178ha in 1996. The other classes of soil use and occupation (reforestement areas, uncovered and affected by fire and humid areas) added were smaller than 4,27% in 1996.
Dynamics of soil occupation of the river Itiquira basin, Mato Grosso, Brazil
Keywords: Itiquira basin; Mato Grosso; Multitemporal analysis; Pantanal; Soil use; land use; occupation; remote sensing; satellite imagery; temporal analysis; vegetation dynamics; Brazil; Itiquira Basin; South America; Western Hemisphere; World